The Popes on Air The History of Vatican Radio from Its Origins to World War II - Perin, Raffaella (World War II: The Global, Human, and Ethical Dimension, 2024)
The story of the origin of Vatican Radio provides a unique look at the history of World War IIThe book offers the first wide-ranging study on the history of Vatican Radio from its origins (1931) to the end of Pius XII's pontificate (1958) based on unpublished sources. The opening of the Secret Vatican Archives on the records regarding Pius XII will shed light on the most controversial pontificate of the 20th century. Moreover, the recent rearrangement of the Vatican media provided the creation of a multimedia archive that is still in Fieri.This research is an original point of view on the most relevant questions concerning these decades: the relation of the Catholic Church with the Fascist regimes and Western democracies; the attitude toward anti-Semitism and the Shoah in Europe, and in general toward the total war; the relationship of the Holy See with the new media in the mass society; the questions arisen in the after-war period such as the Christian Democratic Party in Italy; the new role of women; and anti-communism and the competition for the consensus in the social and moral order in a secularized society